DAMPAK POSISI KERJA PADA KESEHATAN PETANI PEREMPUAN SUKU MARIND-ANIM - Indah Widanarti (Universitas Musamus, Merauke, Papua, 2014)
This research done on which tribe Marind-anim in farming is generally carried out by women.The majority of the tribe marind anim having high body above 165 cmThe research was done starting from august 15 2012 until 12 may 2013.Pulse sample measured to see the level of employment sample.The purpose of this research to identify the body of woman resilience tribe marind-anim in the process of land management by using traditional agricultural tools in the form of a hoe that is in working in posisis often bent.